A viscosity prediction model for cement paste with nano-SiO2 particles. (10th October 2018) - Ouyang, Jian; Han, Baoguo; Chen, Guangzhao; Zhao, Lizhi; Ou, Jinping
Graphical abstract: Highlights: Effect of nano-SiO2 particles dosage and W/C on the viscosity of cement paste is studied. An original viscosity model is proposed to predict the viscosity of nano-SiO2 suspension. Relation of viscosity with nano-SiO2 dosage and W/C is established about cement paste. Limitation of the proposed viscosity model is discussed. Adsorbed water layer thickness of nano-SiO2 particles can be calculated by the model. Abstract: The workability of cement paste with nano-SiO2 (NS) particles depends on NS dosage and water to cement ratio (W/C). To characterize the workability of cement paste with hydrophilic NS particles, the viscosity of cement paste with different NS dosages and W/C is studied. An original viscosity prediction model is proposed to predict the minimum apparent viscosity of cement pastes with different NS dosages and W/C. In this viscosity prediction model, cement paste with NS can be taken as a suspension, i.e. cement particles is suspended in NS suspension. Therefore, the viscosity of cement paste with NS is composed of the viscosity of NS suspension and the relative viscosity of pure cement paste. The viscosity prediction models for NS suspension and pure cement paste are built up, respectively. The limitation of the viscosity prediction model of cement paste with NS is also discussed. Results show the proposed viscosity prediction model has high accuracy in predicting the viscosity of cement pastes with hydrophilic NS when NS volume fraction in NS suspension is less than 5.5%. The adsorbed water layer thickness of NS particles can be also calculated by the proposed model, and it is well in agreement with the mixing state results of NS suspension.